Columnar cell lesions of the breast: a practical review for the pathologist - Angela Flavia Logullo; Cristiane Nimir (BMC, 2019)
Abstract Background Columnar cell lesions (CCLs) of the breast are characterized by the substitution of regular layer of cuboid epithelial by columnar cells covering the terminal duct lobular units (TDLUs). It also comprises a spectrum of lesions characterized by enlarged TDLUs with variably dilated acini lined by columnar epithelial cells, ranging from one or two layers of benign epithelium to stratified epithelium with atypia. With the increasing use of mammography screening scans in the last 30 years, columnar cell lesions (CCLs) have been diagnosed more frequently, often associated with microcalcifications and abnormal calcifications, requiring breast biopsies. This literature review presents the historical development of this entity description, with many terminologies, the CCLs categories, differential diagnoses, immunohistochemical profile and genetic alterations, reproducibility and clinical implications. In addition it discusses the significance of flat epithelial atypia (FEA), a CCL with low-grade cytological atypia. Practical considerations FEA are a frequent finding in breast biopsies and should be a warning sign for other possible entities within the lesion area. Since CCLs are an increasingly recognized entity in the diagnostic spectrum of breast proliferative lesions, proper training or tutorials are advisable for general pathologists in order to teach them how to identify CCLs with confidence. Intraductal proliferations with architectural complexities such as cribriform patterns, rigid cellular bridges, and true micropapillary pattern should not fall into the FEA category and are best classified as atypical ductal hyperplasia (ADH) or ductal carcinoma in situ (DCIS). Conclusions Among CCLs, FEA actually receives more attention due to atypia involved. FEA has been considered a non-obligate pre-neoplastic lesion and progression of these lesions to invasive cancer has been reported as increasingly low (2-7%). Therefore, controversy to the management of those lesions still remains and further intervention is restricted to cases with other premalignant lesions (ADH, DCIS) or in radiologic-pathologic disagreement.